Biological nitrogen fixation of fabaceae in acid soils of Tabasco, Mexico - Córdova-Sánchez, Samuel; Cárdenas-Navarro, Raúl; Peña-Cabriales, Juan José; Salgado-García, Sergio; Castelán-Estrada, Mepivoseth; Lobbit-Phellipe, Cristian; Vera-Núñez, José Antonio (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Biological nitrogen fixation is a process that occurs in nature and is the cheapest source of N for humid tropical acid soils. The aim of this study was to quantify the amount of N fixed by species of fabaceae through 15N isotopic techniques, in a savanna soil in Mexico. The treatments were established under a design of a randomized complete block, with four replicates. The variables evaluated were: fresh biomass (FB), dry matter (DM), nodule number (NN), nodule dry mass (NDM), total nitrogen (tN) and biologically fixed nitrogen (fN). Our results show that Mucuna deerengiana L. had higher production of FB and DM (17.50 and 5.47 Mg ha-1), NDM (58.79 mg plant-1) and higher content of tN and fN (526.94 and 522.11 kg ha-1) respectively, compared with Cajanus cajan L., Phaseolus lunatus L. and Sesbania emerus L., species that showed low values in these variables. We conclude that Mucuna deerengiana L. tolerates unfavorable factors prevailing in acid soils and therefore has efficiency greater than 500 kg ha-1 fN; we consider it appropriate to increase the level of nitrogen in savanna soils, without applying chemical fertilizers.